Lydbøker, plattformlogikk, litteraturpolitikk - Prytz, Øyvind (K&K - Kultur og Klasse, 2024)
The article argues that the subscription-based streaming services for literature in Norway, and the increased use of audiobooks that the streaming services facilitate, must be understood in the light of the platform concept and the media logic that the platforms bring with them. It is not the audiobook format itself that challenges the literary policy goals of diversity, quality, and accessibility, but rather the usage patterns that the streaming services facilitate, the interface in the mobile applications, and the algorithmic recommendations that the platforms offer. Still, the situation is not clear-cut: In many ways, the field of literature in Norway is both paper book-based and consensus-oriented, and there is a clear political will to regulate the platforms and to protect the written word. Examining the Norwegian audiobook field using the concept of platform contributes both to a more nuanced understanding of the audiobook as a medium, and a more nuanced understanding of the platforms’ effects on the dominant patterns of cultural production and cultural consumption.